Find the maximium constant k such that the following inequality is always true for all positive real numbers a , b , and c such that min ( a b , b c , c a ) ≥ 1 :
3 ( a 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) ≤ ( k a + b + c ) 2 + 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We first show the following.
Claim 1 : For any positive real numbers x , y with x y ≥ 1 , we have
( x 2 + 1 ) ( y 2 + 1 ) ≤ ( ( 2 x + y ) 2 + 1 ) 2 . . . . ( 2 ) .
Proof : Note that x y ≥ 1 implies ( 2 x + y ) 2 − 1 ≥ x y − 1 ≥ 0 . We find that
( x 2 + 1 ) ( y 2 + 1 ) = ( x y − 1 ) 2 + ( x + y ) 2 ≤ ( ( 2 x + y ) 2 − 1 ) 2 + ( x + y ) 2 = ( ( 2 x + y ) 2 + 1 ) 2 .
WLOG assume that a ≥ b ≥ c . This implies a ≥ 1 . Let d = 3 a + b + c , Note that
a d = 3 a ( a + b + c ) ≥ 3 1 + 1 + 1 = 1 .
Then we can apply ( 2 ) to the pair a , d and the pair b , c . We get
( a 2 + 1 ) ( d 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) ≤ ⎝ ⎛ ( 2 a + d ) 2 + 1 ⎠ ⎞ 2 ⎝ ⎛ ( 2 b + c ) 2 + 1 ⎠ ⎞ 2 . . . . . . ( 3 )
Next from
( 2 a + d ) . ( 2 b + c ) ≥ a d . b c ≥ 1 ,
we can apply ( 2 ) again to the pair ( 2 a + d , 2 b + c ) . Together with ( 3 ) , we have
( a 2 + 1 ) ( d 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) ≤ ⎝ ⎛ ( 4 a + b + c + d ) 2 + 1 ⎠ ⎞ 4 = ( d 2 + 1 ) 4 . .
Therefore, ( a 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) ≤ ( d 2 + 1 ) 3 . , and the below expression follows by taking the cube root of both above sides.
3 ( a 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) ≤ ( 3 a + b + c ) 2 + 1 .
Is there a non-Jensen way to solve this?
Log in to reply
Indeed see my new solution.
Problem Loading...
Note Loading...
Set Loading...
[Only 1st part of the solution]
Assume that a = b = c = 1 . Then it's obvious that k ≤ 3 .
Now let's prove that ( a + b + c ) 2 + 9 ≥ 9 3 ( a 2 + 1 ) ( b 2 + 1 ) ( c 2 + 1 ) for all a , b , c and we are done.